PENGEMBANGAN POTENSI PARIWISATA, EKONOMI LOKAL BERBASIS E-COMMERCE KAWASAN WISATA GUNUNG IJEN KAB. BANYUWANGI - Riski Isminar Ardianti (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2016)
The era of globalization make the move into tourism industry's largest and strongest in the financing of the global economy. The development of tourism has three functions Promote the economy; Maintaining the national identity and preservation of function and quality of the environment; foster a love for the homeland and the nation. Rapid technological advances that make more rapid dissemination of information. The purpose of the study is to examine the promotion of e-commerce can increase the number of tourist visits in the tourist area of Mount Ijen and through the increase in traffic would improve the welfare of local communities. The study population was a tourist visitor Mount Ijen by taking the sampling method using a random sampling of 350 samples, data collection techniques using questionnaires and interviews. Methods of qualitative and descriptive analysis using bivariate analysis. The results of this study indicate that the tourism promotion Ijen crater through e-commerce can increase the number of tourist visits. Ijen crater tourism information through the Internet easier and cheaper to obtain travel information. With the increasing number of tourist visits Ijen crater members positive impact on the welfare of local communities, especially sulfur miners who were around tourist sites Mount Ijen. Keyword : E-commerce, Tourism, local economic